Community Empowerment Through Improving Weaving Skills to Support the Achievement of Sustainable Development Goals (SDGs) - Barus, Diana Alemin; Gustanto; Masmur, Indra; Tua Raja Simbolon (Talenta Publisher, 2025)
Sustainable economic growth is a challenge for Indonesia today. The Universitas Sumatera Utara in Strengthening SDGs promotes decent and inclusive employment opportunities, and enhances sustainable economic growth in Indonesia by working with companies, civil society organisations, and governments to create an environment that supports inclusive economic development and provides fair access to employment opportunities. The community service team through the community service institution of the Universitas Sumatera Utara plays an active role in the success of the SDGs by carrying out community service with MSME partner Kilang Tenun Sinaga. The results of the team's observations that Kilang Tenun Sinaga MSMEs have such important problems, namely the difficulty of finding employees with skilled weaving skills that cause a lack of weaving production processes that can be fulfilled when ordered, lack of employees who can increase production results, unable to expand by opening new promotional outlets while promoting production results. The solution presented by the team is to carry out community empowerment through improving weaving skills so that they will get the expected employees. This community service team with partners also through this service aims to continue weaving skills, especially ulos motifs, to become part of the world heritage in the future. From this solution, employees also get decent work and improve the community's economy in accordance with SDGs goal no. 8, namely decent work and economic growth.